Crystal structure of an intracellular protease from Pyrococcus horikoshii at 2-Å resolution - Du, Xinlin (The National Academy of Sciences, 2000)
The intracellular protease from Pyrococcus horikoshii (PH1704) and PfpI from Pyrococcus furiosus are members of a class of intracellular proteases that have no sequence homology to any other known protease family. We report the crystal structure of PH1704 at 2.0-Å resolution. The protease is tentatively identified as a cysteine protease based on the presence of cysteine (residue 100) in a nucleophile elbow motif. In the crystal, PH1704 forms a hexameric ring structure, and the active sites are formed at the interfaces between three pairs of monomers.